ՀԲԸՄ-Ի Կահիրէի կառոյցի ցուցաբերած օգնութիւնը Պորտ Սայիդում ապաստանած արեւմտահայ գաղթականութեանը 1915—1918 թթ - Կոնինեան, Մանէ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Геноцидальная политика, осуществляемая Османским режимом в начале XX века, привела к разрушительным последствиям для западных армян. В этих условиях Всеармянский благотворительный союз (ВБС) сыграл ключевую роль в оказании всесторонней помощи беженцам и сиротам, пережившим катастрофу. В 1915—1918 гг. Каирское отделение АГБУ организовало масштабную гуманитарную деятельность, направленную на обеспечение питанием, жильём, медицинским обслуживанием и образованием тысяч армян. После подписания Мудросского перемирия ВБС расширил свои инициативы, уделяя особое внимание репатриации беженцев, уходу за сиротами, а также освобождению армянских женщин и детей, удерживаемых в мусульманских семьях. Деятельность организации выходила за рамки материальной поддержки, стремясь к духовному и культурному возрождению западноармянской общины. ВБС проводило системную работу по сохранению армянской идентичности, национальных ценностей и обеспечению интеграции уцелевших в новые общественные условия. The genocidal policy pursued by the Ottoman regime in the early 20th century had devastating consequences for the Western Armenian population. In response to this humanitarian crisis, the Armenian General Benevolent Union (AGBU) assumed a central role in providing multifaceted support to survivors, particularly refugees and orphans. Between 1915 and 1918, the AGBU Cairo Branch undertook extensive humanitarian initiatives, offering food, shelter, medical aid, and education to thousands of displaced Armenians. Following the Mudros Armistice, the organization significantly broadened its scope of operations. Particular emphasis was placed on the repatriation of refugees, the care and upbringing of orphaned children, and the rescue of Armenian women and minors held in Muslim households. Beyond addressing material needs, AGBU’s mission encompassed the spiritual and cultural rehabilitation of the fragmented Western Armenian community. Through well-coordinated efforts, the organization sought to preserve Armenian cultural identity, promote continuity of national values, and facilitate the integration of survivors into new sociocultural environments.
Keywords: Բարեգործություն; Հայ գաղթօջախների պատմութիւն